Effectiveness of PsikoTalk Blog Media in Preventing Mental Blocks for Islamic Senior High School Students - Durrotul Hikmah; Sopiah; Salwa Solihah; Alin Amalia Kamila; Hidayati Hasina; Siti Chumaerotur Rofiatur Risqoh; Khaerun Umam (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2026)
This study aims to examine the effectiveness of the PsikoTalk blog in preventing mental blocks among students at Assalaam Integrated Islamic Senior High School, Pekalongan. The scope of this study includes the process of implementing blog media as an educational tool that emphasizes students’ psychological and reflective aspects in the context of boarding education. The study used a quantitative approach with a one-group pretest-posttest design. The research subjects were 25 students selected purposively. Data collection was carried out using a mental block scale questionnaire, and the data were analyzed using a Wilcoxon Signed Rank Test in SPSS. The analysis results showed a significant difference between the pretest and posttest scores (p < 0.05) with an effect size value of 0.797 which is categorized as a large effect. These findings indicate that using the PsikoTalk blog effectively reduces mental blocks among students and increases motivation and readiness to learn. Thus, the PsikoTalk blog serves as a digital learning innovation that not only strengthens cognitive skills but also supports students’ mental health. The results of this study are expected to serve as a reference for educators in developing technology-based learning media to strengthen students’ character and psychological well-being.